A 4 × 4 butler matrix for 28 GHz switched multi-beam antenna - Orakwue, Stella Ifeoma (2015)
In this paper, a 4 × 4 Butler matrix (BM) switched-beam patch antenna array is designed and discussed. The design is developed on a single layer of Rogers material; RO 5880 with dielectric constant 2.2 and thickness 0.254mm.This makes the designed antenna low cost and easy of fabrication. The four rectangular patches fed by inset microstrip lines are connected to the outputs of the BM. The results show wide bandwidth that covers from 24.67 GHz to 30.2 GHz in all the four inputs, and the highest array gain performance of 10.8 dBi at 28 GHz. The designed switched beam antenna provides a cost effective approach to implement at 28 GHz wireless communications.